Association of vitamin B1 with cardiovascular diseases, all-cause and cardiovascular mortality in US adults - Wen, He; Niu, Xiaona; Zhao, Ran; Wang, Qiuhe; Sun, Nan; Ma, Le; Li, Yan; Zhang, Wei (Frontiers in Nutrition, 2023)
Background: The correlation between dietary vitamin B1 intake and cardiovascular diseases, as well as the all-cause and cardiovascular associated mortality, is not well known. A large-scale data pool was used to examine the aforementioned correlations of Vitamin B1. Methods: This paper analyzed the dietary data from the survey conducted by National Health and Nutrition Examination (NHANES; 1999-2018). The correlation of vitamin B1 intake in each quartile with cardiovascular diseases such as hypertension, coronary heart disease, myocardial infarction, and heart failure was analyzed using multivariate logistic regression models. The hazard ratios for dietary vitamin B1 intake in each quartile along with all-cause and cardiovascular associated mortality were performed using multivariate cox regression analysis setting the lowest quartile (Q1) as a reference. Restricted cubic spline (RCS) method is used to study the nonlinear relationship. The parameters such as age, sex, body mass index (BMI), smoking history, drinking history and blood lipid were taken into consideration when performing stratified analysis. Results: The study enrolled 27960 subjects (the mean following-up time was 9.11 years). After multivariate adjustment, dietary vitamin B1 intake were significantly and linearly associated with myocardial infarction, heart failure and cardiovascular mortality. The results of restricted cubic spline showed that vitamin B1 intake was negatively and nonlinearly associated with hypertension, with the most significant association in quartile 4 (Q4) of vitamin B1 intake. Meanwhile, there was a dose-response correlations indicating that vitamin B1 intake leads to reduced risk of cardiovascular prevalence and mortality from the disease.The stratified analysis showed that the correlation between age ≥ 50 years, overweight, smoking history, drinking history and dyslipidemia was more significant in male patients. Conclusion: There was a gradual trend towards decreasing the risk of cardiovascular disease prevalence and cardiovascular mortality with increasing dietary vitamin B1 intake in large NHANES-based studies. It is especially significant in elderly-aged men, overweight individuals, smokers, drinkers and dyslipidemia patients.